2009
DOI: 10.1111/j.1468-1331.2008.02433.x
|View full text |Cite
|
Sign up to set email alerts
|

Cladribine impedesin vitromigration of mononuclear cells: a possible implication for treating multiple sclerosis

Abstract: Cladribine might achieve, at least in part, its clinical and paraclinical efficacy by inhibiting the migration of inflammatory cells into and within the CNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…For cladribine several studies demonstrated reductions in the release of pro- and anti-inflammatory cytokines, chemokines, and adhesion molecules, as well as a decrease in the cellular migratory capacity of treated cells [1921]. However, these experiments were performed in the presence of cladribine; therefore, toxic effects rather than modulation of cell function could account for the observed changes.…”
Section: Introductionmentioning
confidence: 99%
“…For cladribine several studies demonstrated reductions in the release of pro- and anti-inflammatory cytokines, chemokines, and adhesion molecules, as well as a decrease in the cellular migratory capacity of treated cells [1921]. However, these experiments were performed in the presence of cladribine; therefore, toxic effects rather than modulation of cell function could account for the observed changes.…”
Section: Introductionmentioning
confidence: 99%
“…T cells and also impacts on B cells, but has only minor effects on natural killer (NK) cells [36,40]. Recent evidence indicates that cladribine may also impede the influx of T cells into the CNS [41]. The sustained effects of cladribine treatment support the use of an annual, short-course dosing regimen.…”
Section: Mechanism Of Action Of Cladribinementioning
confidence: 98%
“…The same study showed that mean natural killer (NK) cell counts dropped during the first months of cladribine treatment, but recovered after 7 months 29. Cladribine may also impair cellular migration into the CNS 30. Using an in vitro Boyden chamber and fibronectin layer, Kopadze et al, studied the effect of cladribine on the migratory capacity of immunocompetent cells in both MS patients as well as controls.…”
Section: Mechanism Of Action Metabolism and Pharmacokinetic Profilementioning
confidence: 99%